2019
DOI: 10.7189/jogh.09.010413
|View full text |Cite
|
Sign up to set email alerts
|

Capacities of women and men to improve maternal and newborn health: Effect of a community-based intervention package in rural Bangladesh

Abstract: BackgroundDespite improvement in recent decades, maternal and newborn mortality in Bangladesh remain high. A community-based intervention package was initiated in 2009 in Netrokona, a rural district in Bangladesh, to engage individuals, families and communities to improve maternal and newborn health. In this article, we present the effect of the intervention package on improvement of women’s capacities with regard to maternal and newborn health, their husbands’ capacities to effectively support them and use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
(28 reference statements)
0
19
0
Order By: Relevance
“…In this study, too, respondents who made the decision jointly with their husbands are found to have better birth preparedness. It is crucial to state the findings from Bangladesh that it is important to engage husband positively in maternal and newborn health [4]. These engagements might also have cultural influences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, too, respondents who made the decision jointly with their husbands are found to have better birth preparedness. It is crucial to state the findings from Bangladesh that it is important to engage husband positively in maternal and newborn health [4]. These engagements might also have cultural influences.…”
Section: Discussionmentioning
confidence: 99%
“…Birth preparedness and complication readiness (BPCR) is an intervention included by World Health Orgnization (WHO) as an essential element of the antenatal care (ANC) package [3]. The BPCR intervention package based on the WHO IFC framework is effective in building the capacities of women and in engaging men positively in maternal and neonatal health [4]. Birth preparedness includes active preparation and decision-making for childbirth, pregnancy, and postpartum period by pregnant women and their family members [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 635 studies met the initial inclusion criteria. Within these results, 35 articles [ 20 54 ] detailing 28 studies met the revised inclusion criteria. The characteristics of the 35 included articles are summarized in Table 1 and in an expanded Table in Additional file 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The mothers who did not complete referral were unable to recognize infant danger signs. Rahman et al 2019 [ 54 ] Bangladesh CHW CHW meetings with women and courtyard meetings with husbands and community members. Not specified Build capacities of women (promote birth preparedness and complication readiness, increase awareness of rights and MNH needs and increase health providers’ capacity to counsel women) and engage families and communities (male involvement and community involvement).…”
Section: Resultsmentioning
confidence: 99%
“…Being an intervention conducting among care-givers of pregnant women, results may be answered for some contradictions regarding the importance of men and families for maternal health according to previous studies [21,25,26,27,28].…”
Section: Ivdiscussionmentioning
confidence: 97%